2002
DOI: 10.1177/154411130201300403
|View full text |Cite
|
Sign up to set email alerts
|

Cellular, Molecular, and Genetic Determinants of Tooth Eruption

Abstract: Tooth eruption is a complex and tightly regulated process that involves cells of the tooth organ and the surrounding alveolus. Mononuclear cells (osteoclast precursors) must be recruited into the dental follicle prior to the onset of eruption. These cells, in turn, fuse to form osteoclasts that resorb alveolar bone, forming an eruption pathway for the tooth to exit its bony crypt. Some of the molecules possibly involved in the signaling cascades of eruption have been proposed in studies from null mice, osteope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
250
1
39

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(293 citation statements)
references
References 97 publications
(121 reference statements)
3
250
1
39
Order By: Relevance
“…The dental follicle develops from ectomesenchyme. It surrounds the developing tooth germ before eruption (Ten Cate, 1997;Wise, 2002). During embryonic development, the ectomesenchyme is partly derived from migrating cells of the cranial neural crest.…”
Section: Stem Cells For Bone Regenerationmentioning
confidence: 99%
“…The dental follicle develops from ectomesenchyme. It surrounds the developing tooth germ before eruption (Ten Cate, 1997;Wise, 2002). During embryonic development, the ectomesenchyme is partly derived from migrating cells of the cranial neural crest.…”
Section: Stem Cells For Bone Regenerationmentioning
confidence: 99%
“…The dental follicle that lies above the erupting permanent tooth plays a key role in tooth transposition through the mineralized tissue crypt since the follicular cells secrete important chemicals to replenish osteoclasts and odontoclasts in the area. 12,13 In this cascade of molecular signals that regulates tooth eruption within the follicle, Que et al 14,15 demonstrated that the IL-1 family plays a major role. The IL-1 family is comprised of 3 ligands, IL-1a, IL-1b, and IL-1RA, all of which bind the IL-1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Primary teeth will shed (exfoliate) to their permanent successors. Although many theories have been advanced (Marks Jr., 1996;Philbrick et al, 1998;Wise et al, 2002), the factors responsible for the eruption of the teeth are not fully understood. The factors that have been related to the eruption of teeth include elongation of the root, forces exerted by the vascular tissues around and beneath the root, growth of the alveolar bone, growth of dentin, growth and pull of the periodontal membrane, hormonal influences (pituitary growth hormone, thyroid hormone, and parathyroid hormone-related protein), presence of a viable dental follicle, pressure from the muscular action, and resorption of the alveolar crest.…”
Section: Upper Permanent Teeth Development Chart Upper Teethmentioning
confidence: 99%
“…The factors that have been related to the eruption of teeth include elongation of the root, forces exerted by the vascular tissues around and beneath the root, growth of the alveolar bone, growth of dentin, growth and pull of the periodontal membrane, hormonal influences (pituitary growth hormone, thyroid hormone, and parathyroid hormone-related protein), presence of a viable dental follicle, pressure from the muscular action, and resorption of the alveolar crest. A review article by Wise et al (Wise et al, 2002) focused on the molecular signals that initiate tooth eruption. They stated that tooth eruption is a complex and tightly regulated process involving cells of the tooth organ and surrounding alveolus.…”
Section: Upper Permanent Teeth Development Chart Upper Teethmentioning
confidence: 99%